2016
DOI: 10.1108/ijchm-03-2015-0114
|View full text |Cite
|
Sign up to set email alerts
|

Night markets: entrepreneurship and achieving competitive advantage

Abstract: Purpose This paper aims to propose a new model and examine how night market entrepreneurs have achieved a competitive advantage in strongly competitive markets. Design/methodology/approach Two statistics methods, multiple regression analysis and structural equation models (SEM), were used to test the hypotheses for a sample of 346 vendor cases. Findings The results indicate that competitive aggressiveness and being proactive are positively related to risk-taking among night market vendors, which, in turn, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 71 publications
2
17
0
Order By: Relevance
“…Thus, their ICT capability is the companies' ability to utilize digital media or ICT to support their business operations and marketing (Qosasi and Permana 2017). Liu and Fang (2016) argued that having a competitive advantage means that companies can create more economic value than their competitors can (Porter 1985). Newbert (2008) extended Porter's concept and asserted that competitive advantage is the implementation of corporate strategies to achieve cost reduction goals, to exploit market opportunities, and to neutralize competitive threats.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, their ICT capability is the companies' ability to utilize digital media or ICT to support their business operations and marketing (Qosasi and Permana 2017). Liu and Fang (2016) argued that having a competitive advantage means that companies can create more economic value than their competitors can (Porter 1985). Newbert (2008) extended Porter's concept and asserted that competitive advantage is the implementation of corporate strategies to achieve cost reduction goals, to exploit market opportunities, and to neutralize competitive threats.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Advantage (Liu and Fang 2016) 10. Able to combine the resources and the ability to reduce operating costs to a more effective level than those of other similar stores 11.…”
Section: Variablesmentioning
confidence: 99%
“…As a specifically Taiwanese cultural and nightlife phenomenon and one of the three most popular attractions in Taiwan [ 86 ], Shilin Night Market attracts lots of tourists [ 87 ]. In Shilin Night Market, crowded roads, blocked traffic, extremely high crowd density, and many tourists appear frequently.…”
Section: Methodsmentioning
confidence: 99%
“…On the contrary, there are some who believe in tradition and that the nature of the business is to have a sustainable income altogether, disregarding the prospect of modernization, particularly common among hawkers who are older (Omar and Ishak, 2016). These are people who build their business at a young age from the ground up and believe that sustainability in familiarity is better than taking unchartered risk, which may cause mental and physical exhaustion as a consequence of adapting to new knowledge and skills, plus facing the uncertainty of receiving higher profits if modernization was to take place (Chong, 2018; Omar and Ishak, 2016).Studies have confirmed that product innovation and a transformational business mindset are two crucial drivers of successful hawker food businesses (Liu and Fang, 2016; Seraphin et al., 2017; Stevenson et al., 2019). These studies generally indicate that competitive aggressiveness and being proactive are positively related to risk-taking among street food vendors, having a constructive effect on innovativeness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These studies generally indicate that competitive aggressiveness and being proactive are positively related to risk-taking among street food vendors, having a constructive effect on innovativeness. Further, risk-taking has a mediating role to play in innovativeness, which can produce competitive advantages (Liu and Fang, 2016). Seraphin et al.’s (2017) study on the identification of typical successful attributes of food tourism enterprises, confirms that transformational entrepreneurs and enterprises with constant collaboration with key stakeholders could effectively provide high-quality products and services, particularly through the implementation of unique product differentiation strategies that are different than other competitors.…”
Section: Literature Reviewmentioning
confidence: 99%